2020
DOI: 10.1101/2020.08.31.276261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional kinetic synergy: a complex landscape revealed by integrating modelling and synthetic biology

Abstract: 1AbstractEukaryotic genes are combinatorially regulated by a diversity of factors, including specific DNA-binding proteins called transcription factors (TFs). Physical interactions between regulatory factors have long been known to mediate synergistic behaviour, commonly defined as deviation from additivity when TFs or sites act in combination. Beyond binding-based interactions, the possibility of synergy emerging from functional interactions between TFs was theoretically proposed, but its governing principles… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 125 publications
1
22
0
Order By: Relevance
“…Indeed, thermodynamic models have been employed to interrogate the regulatory function of eukaryotic promoters involved in key processes such as cellular differentiation, body patterning, and a host of other biological roles ( Segal et al, 2006 , 2008 ; Sayal et al, 2016 ; Chen et al, 2008 ; Ay and Arnosti, 2011 ; Fakhouri et al, 2010 ; Bashor et al, 2019 ). The ability to distinguish and quantify the different modes of regulation (stabilization and acceleration) and characterize TFs based on them is important for developing general theories of regulation that include multiple TFs that act on different kinetic steps of the transcription process ( Scholes et al, 2017 ; Martinez-Corral et al, 2020 ; Wong and Gunawardena, 2020 ); predictions for the combined regulatory effect of two stabilizing TFs should be different than predictions for a stabilizing TF acting together with an accelerating TF ( Scholes et al, 2017 ). With each characterized TF, we can develop an empirical baseline or null hypothesis for what a TF should do on a gene; departures from this expectation, because of emergence of complex regulatory phenomenon brought about by TF-TF interactions ( Weingarten-Gabbay and Segal, 2014 ), allosteric interactions ( Rosenblum et al, 2020 ; Kim et al, 2013 ), or other effects indicate surprises that warrant testing in these expanded models.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, thermodynamic models have been employed to interrogate the regulatory function of eukaryotic promoters involved in key processes such as cellular differentiation, body patterning, and a host of other biological roles ( Segal et al, 2006 , 2008 ; Sayal et al, 2016 ; Chen et al, 2008 ; Ay and Arnosti, 2011 ; Fakhouri et al, 2010 ; Bashor et al, 2019 ). The ability to distinguish and quantify the different modes of regulation (stabilization and acceleration) and characterize TFs based on them is important for developing general theories of regulation that include multiple TFs that act on different kinetic steps of the transcription process ( Scholes et al, 2017 ; Martinez-Corral et al, 2020 ; Wong and Gunawardena, 2020 ); predictions for the combined regulatory effect of two stabilizing TFs should be different than predictions for a stabilizing TF acting together with an accelerating TF ( Scholes et al, 2017 ). With each characterized TF, we can develop an empirical baseline or null hypothesis for what a TF should do on a gene; departures from this expectation, because of emergence of complex regulatory phenomenon brought about by TF-TF interactions ( Weingarten-Gabbay and Segal, 2014 ), allosteric interactions ( Rosenblum et al, 2020 ; Kim et al, 2013 ), or other effects indicate surprises that warrant testing in these expanded models.…”
Section: Discussionmentioning
confidence: 99%
“…We find that the contributions of these two mechanisms do not correlate with position; in some locations we found sta- Here we focus entirely on the isolated regulatory role of each TF, however it is clear that one of the next steps is to probe how quantified TFs regulate together. the ability to distinguish and quantify the stabilization and acceleration mode of regulation and characterize TFs based on them is important for developing general theories of regulation that include TFs acting on different kinetic steps of the transcription process [77,78,79]; predictions for the combined regulatory effect of two stabilizing TFs should be different than predictions for a stabilizing TF acting together with an accelerating TF [77]. With each TF characterized, we can develop an empirical baseline or null hypothesis for what a TF should do on a gene: departures from this expectation, due to the emergence of complex regulatory phenomenon brought about by TF-TF interactions [63], allosteric interactions [80,81] or other effects indicate surprises that warrant testing in these expanded models.…”
Section: Discussionmentioning
confidence: 99%
“…What happens to an output function on G ? It can be shown that, provided G itself is at thermodynamic equilibrium, any output function on G can be rewritten as a non-negative linear combination of steady-state probabilities of C ( G ),iνfalse(Cfalse(Gfalse)false)λiuifalse(Cfalse(Gfalse)false),1emλi0,where, crucially, the coefficients λ i do not depend on x , as long as G is at thermodynamic equilibrium [78]. Comparing with equation (5.1), we see that equation (5.4) defines an input–output function on C ( G ), which, as noted above, has the hypercube structure scriptCm.…”
Section: Hopfield Barriers Coarse Graining and Hill Functionsmentioning
confidence: 99%
“…Equilibrium parameter values are randomly chosen in some range, the corresponding false(p, sfalse) points calculated and the resulting point cloud is incrementally grown until a boundary is reached. The algorithms are elaborated in [14,15,78]. Part of the equilibrium position–steepness region for the regulated-recruitment gene-regulation model described above, based on the hypercube structure scriptC4+1, is shown in figure 3 c .…”
Section: Hopfield Barriers Coarse Graining and Hill Functionsmentioning
confidence: 99%